P220 Opportunities and challenges to the rituals of care that circumvent misdiagnosis amongst rapid HIV testers in zimbabwe. (14th July 2019) - Skovdal, Morten; Beckmann, Nadine; Maswera, Rufurwokuda; Nyamukapa, Constance; Gregson, Simon
Abstract : Background: There is uncertainty associated with all medical testing and diagnosis. However, a growing number of studies highlight disconcerting levels of misdiagnosis in the scale-up of HIV rapid testing programmes. Evaluation studies point to user errors as potential sources of misdiagnosis, yet very little has been done to understand the views and experiences of clinicians and primary counsellors who perform rapid HIV testing. Methods: This study draws on interviews with 28 health facility staff who perform rapid HIV tests on a daily basis. The testers were recruited from 11 health facilities across Zimbabwe, eight of which have above average rates of misdiagnosis. Interviews were translated, transcribed and thematically interrogated. Results: Reflecting on their rapid HIV testing practices, potential sources of misdiagnosis included uncertainties associated with new testing algorithms and test kits; reading test results too quickly or too late; misreading of test results if the test produces faint or unclear lines; and failure to record and document test results accurately. Anxiety about potentially making such mistakes and the resulting feelings of guilt and self-blame in the case of a wrong diagnosis being handed out meant that testers found comfort in complying with standard operating procedures and associated quality controls. Misdiagnosis was thus portrayed as a result of deviating from 'rituals of care'. The testers located deviance from the procedures in the wider context of high workloads and growing demands for HIV testing, arguing that distractions, and HIV test kit stock-outs occasionally made it difficult for testers to follow the procedures. Conclusion: Rather than attributing misdiagnosis to malfunctioning test kits or complicated standard operating procedures, testers saw misdiagnosis largely as human error – failure to follow laid out procedures. Their recognition of how a resource-depleted work and HIV testing environment can contribute to misdiagnoses, highlight the need to adequately resource HIV rapid testing programmes. Disclosure: No significant relationships.